Synthesis and photocatalytic properties of CeVO4nanoparticles under UV irradiation - P. Intaphong (2018)
© 2015, Inst Materials Physics. All rights reserved. In this research, CeVO4nanoparticles have been successfully synthesized by hydrothermal reaction. The as-synthesized CeVO4nanoparticles were characterized by X-ray powder diffraction (XRD), Raman spectroscopy, Fourier transform infrared (FTIR) spectrophotometry and scanning electron microscopy (SEM). The photocatalytic activity of the as-synthesized CeVO4nanoparticles was evaluated via the photodegradation of methylene blue (MB) under UV irradiation. In this research, the tetragonal CeVO4nanoparticles with the particle size less than 100 nm were detected. The V–O stretching and bending in VO43–tetrahedrons were detected by FTIR and Raman spectrometry. The photocatalysis of MB by CeVO4nanoparticles exhibited the decolorization efficiency of 80 % within 300 min.